Mobius Syndrome and Autistic Spectrum Disorder - J Gordon Millichap (Pediatric Neurology Briefs, 2001)
The relation between autistic spectrum disorder and Mobius syndrome was studied in 25 patients (18 males and 7 females) included in a multidisciplinary study of Mobius sequence at the Department of Child and Adolescent Psychiatry, Goteborg University, Sweden.